2020
DOI: 10.1002/jhbp.791
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of regional lymph node metastasis according to station in ampullary carcinoma

Abstract: Patients with ampullary carcinoma have a better prognosis than those with the other biliary tract carcinomas. 1-4 Ampullary carcinoma is usually detected at a relatively early stage and is often resectable at the time of diagnosis, unlike other types of biliary tract cancer. 4-6 The TNM (Tumor, Node, Metastasis) classification of the Union for International Cancer Control (UICC) is used worldwide for cancer staging; in the 8th edition, the regional lymph nodes for ampullary carcinoma are the same as those for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In previous studies, several predictors of LNM in resected AVC have been described including number of retrieved LNs, ratio of positive LNs/retrieved LNs, number of metastatic LNs (based on UICC N stage classi cation), and location of regional LNs (pancreatic head or except for pancreas head) [5,6,[18][19][20]. Matui et al reported that regional LNM, except to the pancreatic head region, was associated with poor prognosis, comparable to that of patients with M1-stage [21].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, several predictors of LNM in resected AVC have been described including number of retrieved LNs, ratio of positive LNs/retrieved LNs, number of metastatic LNs (based on UICC N stage classi cation), and location of regional LNs (pancreatic head or except for pancreas head) [5,6,[18][19][20]. Matui et al reported that regional LNM, except to the pancreatic head region, was associated with poor prognosis, comparable to that of patients with M1-stage [21].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical features of the patients are shown in Table I. Patients with head and neck cancer were divided into four stages, according to tumor-node-metastasis (TNM) ( 17 ) and differences in TMEM158 expression at different Tumor-Node-Metastasis stages were analyzed. RNAInter software ( ; Department of Bioinformatics, Southern Medical University) was used to predict the target association between miR-548ac and TMEM158.…”
Section: Methodsmentioning
confidence: 99%
“…This facilitates complete dissection of station 17 nodes, which are the first group of involved lymph nodes in periampullary and pancreatic cancer. [ 3 ] Once the mesenteric division reaches the first jejunal vein, further dissection is done along the wall of the first jejunal vein. PIPDV joining the first jejunal vein close to its confluence with SMV is ligated and divided [ Figure 6 ].…”
Section: Operative Stepsmentioning
confidence: 99%